Macroeconomic and Structural Policies in Fund-Supported Programs : Review of Experience. (Policy Papers; Policy Paper, 2004)
A Fund-supported program is a package of envisaged policies which, combined with approved financing, is expected to achieve certain economic objectives such as fostering macroeconomic stability and orderly external adjustment, promoting growth and poverty reduction, and reducing vulnerability to future balance of payments problems or financial crises. This paper reviews experience with specific macroeconomic and structural policies intended to achieve these objectives.